Dual-tasks in soccer: Effects of players` experience and task condition on physical performance - Praça, G. M.; de Almeida Oliveira, P. H.; Santos Resende, V. H. (Perceptual and Motor Skills, 2024)
In this study, we examined whether experience level and various dual motor and cognitive or single tasks influenced young soccer players` physical performance during small-sided games. Participants were 72 players from U-13 (n = 36) and U-17 (n = 36) groups who participated in 3-to-a-side small-sided games under four experimental conditions: control, a secondary motor task, an additional related secondary cognitive task, and an additional secondary non-specific task. We used GPS devices to measure physical performance in terms of distances covered and accelerations at different thresholds. We found no significant interaction effect between player experience and task condition (p = .540), meaning that dual tasks had comparable effects on players of different experience levels. There were significant main effects of both experience level (p < .001) and condition (p < .001) on most physically related variables. Older players outperformed younger ones, particularly in high-intensity actions. While secondary motor tasks decreased physical performance, secondary cognitive tasks, irrespective of specificity, did not impair players` performances. In conclusion, experience level did not influence the players` physical response to dual tasks, and a secondary motor task was more disruptive to physical performance than either of two types of secondary cognitive tasks. Cognitive tasks can be incorporated into soccer training without compromising physical performance.